Корпоратизація сфери надрокористування в Україні - Пугач, В.О. (Економіка природокористування і охорони довкілля, 2013)
Проаналізовані поняття корпоратизації, у загальному досліджена корпоративна сфера надрокористування в Україні, а також деструктивні чинники, які негативно впливають на цю галузь. Наведені необхідні заходи щодо вдосконалення функціонування корпоративного сектору надрокористування. The article analyzes the concept of corporation, broadly viewed corporate industry of subsoil use in Ukraine and destructive factors that negative influence on this industry. These are necessary measures to improve the functioning of the corporate sector subsoil: improve the business climate, improvement of financial and credit system, minimizing the informal sector of the national economy, promoting fair competition, support innovation and investment.